PEMANFAATAN TEPUNG AMPAS KELAPA SEBAGAI SUBSTITUSI PEMBUATAN BOLU KERING: Utilization of coconut daste flour as a substitution for dry bolu production - Salindri Salindri (PAKIS JOURNAL INSTITUTE, 2023)
Processed coconut pulp, which is made into flour with rich fiber, can be used as a substitute for flour in the manufacture of dry sponge cakes. The purpose of this study was to determine the level of preference (taste, color, texture, and aroma) for each substitution of coconut dregs in processed food, namely dry sponge cake. The process of making coconut dregs flour was dried in an oven at 70 °C, mashed, and then used as a substitute for wheat flour in processed dry cakes with substitutions of 20%, 25%, 30%, 35%, and 40%. The treatment used was the addition of coconut pulp flour and wheat flour with a ratio of F1 (20% : 80%), F2 (25% : 75%), F3 (30% : 70%), F4 (35% : 65%), and F5 (40% : 60%), then analyzed for fiber content. The results of the data obtained were then analyzed using the SPSS program by testing for normality and correlation tests on the parameters of fiber content with the parameters of taste, color, texture, and aroma, and tabulated in the form of tables, residual plots, contour plots, and radar. The results of the identification of the preference level of dry sponge cake with coconut dregs flour substitution were more dominated by F1 treatment (20% coconut dregs:80% wheat flour). The fiber content in the dry sponge cake using coconut dregs flour substitution ranged from 7.01% to 11.71%. In addition, the correlation results obtained between the fiber content and the results of the preference level test indicate that the relationship between parameters has a relationship or correlation. The identification results from this study showed that the variation in coconut dreg flour substitution in the manufacture of the dry cake was greater in product samples F1 (taste, color, and texture) and F5 (aroma).